Profitability analysis of backgrounding and finishing of beef cattle in western amazon: a multiple-case study - Nobile, Camilla Birenbaum; Brandão Reis, Eduardo Mitke; Linhares, Luane Pereira; De Oliveira, Antonia Valcemira Domingos; Lopes, Marcos Aurélio; Rosa, Bruna Laurindo [UNESP]; Beber, Paulo Márcio (Universidade Estadual de Londrina, 2022)
This study aimed to evaluate the economic profitability of farms for backgrounding and finishing of beef cattle located in the mesoregion of Acre valley, in a multi-case study format. The data used originated from three pre-selected farms from January to December 2018. Data were collected from an inventory of assets and cash flow, which were later tabulated in Excel® software using descriptive statistics through mean, percentage, and standard deviation to present the indicators. The average effective operating cost (EOC) was BRL 1,399,014.34 and the total operating cost (TOC) was BRL 1,444,068.53 and the total cost (TC) was BRL 1,673,860.38. The items that compose the EOC which exerted greater representation on the activity costs were the purchase of animals (79.6%), food (7.8%), and labor (5.9%), respectively. Under these conditions, the three properties studied showed positive gross margins, net margins, and positive results, indicating their profitability in the short, medium, and long term, with possibilities for expansion in the region.
Análise da rentabilidade de sistemas de recria e engorda de bovinos de corte na amazônia ocidental: estudo de múltiplos casos
Keywords: Acre; Livestock; Production cost; Profitability